Lesson as the Main Component of the Educational Process - Rokhila Sherkulovna Kuziboyeva (International Journal of Formal Education, 2025)
This article examines the issues of methodology of teaching Russian as a foreign language. The goals and conditions of training are defined, the factors determining the effectiveness of teaching Russian as a foreign language are shown.